(untitled) (REMUNOM, 2025)
The increasing use of Artificial Intelligence (AI) in education is reshaping pedagogical practices, offering personalized learning and optimization of administrative processes. This article investigated, through a systematic literature review, the impact of AI on teacher training and teaching-learning processes, aiming at the transformation of traditional pedagogical methods. The results highlight that AI, utilizing tools like learning analytics and machine learning, provides adaptive personalization of teaching, adjusting content and pace to individual needs, thus favoring inclusion and the early detection of difficulties. However, crucial challenges persist, such as the urgent need for specialized teacher training for the ethical and responsible use of technology. Furthermore, the study raises ethical concerns, including algorithmic biases related to race and gender, and the centralization of power in Big Techs, which threatens digital sovereignty and educational equity. It is concluded that the successful integration of AI requires consistent policies and a balance between technological innovation and human, ethical, and equitable principles, mediated by education professionals.